North American survey and systematic review on caudal Septoplasty - Béatrice Voizard; Mélanie Theriault; Selma Lazizi; Sami P. Moubayed (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Surgical correction of caudal septal deviation is a technically challenging step of functional rhinoplasty. Multiple surgical techniques have been described in the literature but comparing the efficacy of each in relieving obstruction presents a challenge. Outcome measures are necessary to adequately compare techniques. This study aims to describe the current caudal septoplasty techniques of Otolaryngologists and Facial plastic and reconstructive surgeons (FPRS), as well as their use of outcome measures, and to compare these practices with surgical trends described in the literature. Methods An online survey was sent to three Otolaryngology and FPRS associations in Canada and the United States. A systematic review was conducted on SCOPUS and PubMed to classify the caudal septoplasty techniques described in the literature and the outcome measurement tools used. Results Our survey identified that caudal septoplasty is more commonly performed by surgeons with an FPRS training background. The most common techniques were the swinging door technique (69.5%), extracorporeal septoplasy (46.7%), cartilage scoring (45.3%), and splinting with bone (25.4%). Despite using a vast array of surgical techniques, North American physicians rarely rely on standardized outcome assessment tools. Patient reported outcome measures (PROMs) are used almost twice as frequently in the literature as they are by surgeons in their clinical practice. Conclusion We recommend that future studies of caudal septoplasty include an assessment of both form and function using a validated PROM such as the Standardized Cosmesis and Health Nasal Outcomes Survey.